Gibberellic and Indole Acetic Acids Producing Features of Bacteria from the Genus Lactobacillus and their Effect on Plant Development - Turaeva, Bakhora Ismoilovna; qizi, Kamolova Khulkar Fozil; Soliev, Azamjon Bakhodirovich; Kutlieva, Guzal Jumaniyazovna (Asian Journal of Biological and Life Sciences)
Gibberellic acid (GA), also known as gibberellin A3, GA, and GA3, and indole acetic acid (IAA) are phytohormones that enhance plant growth and are key properties of soil microorganisms, rhizosphere bacteria, micromycetes, and lactic acid bacteria. In this research work, lactic acidsynthesizing bacteria were isolated from a variety of plants and their effects on the growth of wheat coleoptiles were studied. High growth activity of Lactobacillus bacteria and the formation of GA and IAA were detected by hyphenated HPLC-MS, and its antifungal activity was studied against some phytopathogenic micromycetes. It should be noted that despite the widespread use of lactic acid bacteria, their effect on plant development, their phytohormone forming features have poorly been studied and now, it becomes a new direction in science.
Keywords: Bacillus sp. L. plantarum М-1; Bacteria; L. plantarum М; L. plantarum-D; L. plantarum-G; L. plantarum-S; L. plantarum-V; Lactobacillus; Phytohormones.